HANDLING THE SPIRITUALITY OF SANTRI THROUGH SELF HEALING: STUDY OF THE LIVING QUR’AN AGAINST THE LEMBAGA MOTIVASI NURUL JADID PAITON PROBOLINGGO - Mayanti, Novi Indah; Badriyah, Nur (Universitas Nurul Jadid, 2021)
Pondok Pesantren is an Islamic educational institution that has a vital role in the history of Islam in Indonesia. It also acts as a place to improve students’ spirituality, but the facts in the field are that many students commit deviations. The Lembaga Motivsi Nurul Jadid (LMNJ) is one of the institutions in the Pondok Pesantren Nurul Jadid to deal with student deviations with hypnotherapy and motivation methods that apply the contents of the Qur’an which are made more scientific and not mystical but very logical, readily accepted by all circles, as well as a form of development of the science of the Qur’an within the scope of the pesantren which is relatively rapid with the presentation of the application of the values of the Qur’an in a scientific or modern manner. This research was conducted through a living Qur’an approach to examine the values of the Qur’an contained in LMNJ through self-healing with stages, counselee analysis, motivation support, and spiritual influence. The method used is descriptive qualitative, that is, research that analyzes data by adjusting the phenomena that occur and is then associated with existing theories or opinions. To complement and sharpen this research, it is equipped with field studies and literature.